We are family: designing and developing a mobile health application for the San Francisco bay area House Ball and Gay Family communities - Saberi, Parya (Mhealth, 2020)
BACKGROUND: The House Ball community (HBC) and its affiliated Gay Families (GFs) consist of predominantly African American and Latinx sexual, gender, and ethnic minorities (SGEM), who form chosen families often as a way to provide support, and in the case of the HBC, to constitute houses that then compete in performative categories in balls. Members of both communities are disproportionately impacted by HIV. Although public health professionals have engaged with the HBC and GFs to improve HIV testing and clinical care, most intervention activities have relied on in-person modes of outreach and delivery. Little research has been conducted with the members of the HBC and GFs to develop and produce culturally-informed mobile health (mHealth) applications that would enable them to increase HIV-related knowledge, connect to HIV-related resources, receive HIV health support, and to celebrate their unique identities and communities in a safe space. METHODS: We conducted 45 in-depth interviews with HBC and GF members who attended balls. Topics included HIV-related health needs, suggestions for mHealth components, current usage of apps and desirable features, and wishes around privacy and security. Following analysis of the interview data, we convened a series of four workshops with N=15 participants who were split into two groups. The purpose of the workshops was to co-design a digital tool to help provide information, reduce HIV-related stigma, and locate HIV resources for participants. Each group attended two workshops. Data were analyzed by a team of social scientists, community members, and mobile health experts. Findings were used to design an mHealth app related to HIV prevention and care. RESULTS: Participants requested an app that clearly reflected the community. The desired features of the app included accurate information and education on HIV transmission; links to resources such as HIV testing, lube and condoms, PrEP, and other health-related services; and the ability to rate and review local resources. In workshops, participants proposed several design elements and functions for the app. It had to be ‘Mobile and Modern’, ‘Relatable, Raw, and “Reflective of Me”’, ‘Positive and Fun’, feature community-generated content, and provide a safe space for users. Using these clear directives, the team designed an mHealth tool to be fielded as part of the larger “We Are Family” intervention that would provide HIV-specific information, resources, and support in a platform that was congruent with community norms and expectations. CONCLUSIONS: Designing and fielding an mHealth app as part of a larger HIV prevention intervention that reflects the social support and relationships within existing House Ball and Gay Family communities allows those youth most at risk for HIV-related health disparities to gain access to HIV testing, or link and re-engage young people to care.